2001
DOI: 10.1074/jbc.m011469200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Pterin Antagonism in Nitric-oxide Synthase

Abstract: Pathological nitric oxide (NO) generation in sepsis, inflammation, and stroke may be therapeutically controlled by inhibiting NO synthases (NOS). Here we targeted the (6R)-5,6,7,8-tetrahydro-L-biopterin (H 4 Bip)-binding site of NOS, which, upon cofactor binding, maximally increases enzyme activity and NO production from substrate L-arginine. The first generation of H 4 Bip-based NOS inhibitors employed a 4-amino pharmacophore of H 4 Bip analogous to antifolates such as methotrexate. We developed a novel serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Thus, the addition of the tether rather than the ruthenium(II) complex is likely to be responsible for the increased binding affinity. Indeed, other pterin analogues have been reported that show enhanced binding upon alkylation at the 4‐position,8a, 16 and wires designed for cytochrome P450 from P. putida (P450 cam ) show higher affinities than substrate alone 3b. It is likely that the additional hydrophobic contacts provided by the linker in the access channel are responsible for each of these enhanced affinities.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the addition of the tether rather than the ruthenium(II) complex is likely to be responsible for the increased binding affinity. Indeed, other pterin analogues have been reported that show enhanced binding upon alkylation at the 4‐position,8a, 16 and wires designed for cytochrome P450 from P. putida (P450 cam ) show higher affinities than substrate alone 3b. It is likely that the additional hydrophobic contacts provided by the linker in the access channel are responsible for each of these enhanced affinities.…”
Section: Methodsmentioning
confidence: 99%
“…On comparing main peaks of MDPhTL with its complexes, it is observed that all the signals of the free ligand are present in the 1 H and 13 C NMR spectra of the complexes. In the 13 C NMR spectra of 1-5, the resonances for C-8 (δ 158.7-157.3 ppm), C O (δ 156.4-156.0 ppm), C-6 (δ 148.9-148.0 ppm), and C-8a together with C-7 (145.8-145.1 ppm) were practically unchanged since they lie far from the binding site of the ligand. However, a C 2 S carbon atom of MDPhTL (177.6 ppm) shifted downfield by about 11 ppm compared to the complexes (166.9-161.1 ppm), indicative of MDPhTL in its monoanionic form acts as a chelate coordinating through its S and N-1 donor atoms.…”
Section: Chemistrymentioning
confidence: 97%
“…Several pteridine derivatives have been studied from a variety of perspectives by many different research groups [6][7][8][9]. Recently, Schmidt et al [10][11][12][13] have synthesized various tertrahydropterin analogues with remarkable inhibition of the nitric oxide synthase, the enzyme responsible for the mental disorder. It is known that pteridine and pterin act by inhibiting the xanthin oxidase, as a key enzyme in the biosynthesis of DNA precursors and a generator of free radicals [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of pteridines in the key cofactors, tetrahydrofolate and tetrahydrobiopterin, has encouraged the development of the chemistry and chemical biology of pteridines . The pteridine nucleus is found to be essential component of various compounds possessing biological activities such as anti‐inflammatory , antimicrobial , anti‐hepatitis , immunosuppressive , antitumor , and neurodegenerative agents activities as well as α‐tumor nacrosis factor agents , adenosine kinase inhibitors , and nitric oxide synthase inhibitors . Methotrexate ( 1 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%